Common mental disorders increase pre-eclampsia/ eclampsia risks in pregnancy - Y Wibowo; M Hakimi; CR Marchira (Faculty of Medicine, Universitas Trisakti, 2013)
INTRODUCTION Pre-eclampsia is a multisystem complication that occurs after 20 weeks of pregnancy and can cause considerable maternal and fetal morbidity and mortality. Mental health is influenced by social support, and emotional distress during pregnancy may cause pre-ecclampsia/ecclampsia (PE/E). The objective of this study was to determine the association of social support and common mental disorders (CMD) with PE/E in pregnant women. METHODS This study was a matched case-control study. Cases were pregnant women who had been diagnosed with PE/E. Controls were those with normal pregnancies or not diagnosed as PE/E. Instruments social support questionnaire-6 (SSQ-6) was used to measure social support and self-reporting questionnaire 20 (SRQ-20) items for measuring CMD. Conditional logistic regression was used to estimate matched odds ratios (ORs) and 95% confidence intervals (95% CI). RESULTS Low social support was not directly associated with PE/E. Compared with women with high social support, those with low social support had a 26-fold increased risk of CMD (+) (OR=26.4, 95% CI: 10.67 to 77.20, p=0.001). Several variables significantly associated with PE/E were CMD (+) (OR=6.11, 95% CI: 2.99 to 14.07, p=0.001), low family income (OR=2.93, 95% CI: 1.56 to 5.82, p=0.001), history of chronic hypertension (+) (OR=7.67, 95% CI: 2.32 to 39.89, p=0.001), history of PE/E (+) (p=0.001), and history of hereditary PE/E (+) (OR=6, 95% CI: 1.34 to 55.20, p=0.013). CONCLUSION Low social support was not directly associated with PE/E but was associated with CMD. To prevent CMD in pregnant women, there is a need for social support from the family.